2020
DOI: 10.3389/fnins.2020.602796
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Artificial Light at Night and the Consequences for Flora, Fauna, and Ecosystems

Abstract: The present review draws together wide-ranging studies performed over the last decades that catalogue the effects of artificial-light-at-night (ALAN) upon living species and their environment. We provide an overview of the tremendous variety of light-detection strategies which have evolved in living organisms - unicellular, plants and animals, covering chloroplasts (plants), and the plethora of ocular and extra-ocular organs (animals). We describe the visual pigments which permit photo-detection, paying attent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
87
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 362 publications
(515 reference statements)
0
87
0
6
Order By: Relevance
“…Addressing effects of ALAN is therefore urgent [10,59]. Our data contribute to the rising evidence for dose-dependent responses of behavior and physiology [22,30,60], which might allow mitigating against ALAN impacts on wildlife by reducing light intensity [61].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Addressing effects of ALAN is therefore urgent [10,59]. Our data contribute to the rising evidence for dose-dependent responses of behavior and physiology [22,30,60], which might allow mitigating against ALAN impacts on wildlife by reducing light intensity [61].…”
Section: Discussionmentioning
confidence: 69%
“…For wild animals, our study adds to emerging evidence of detrimental effects of ALAN on physiological pathways [9,10,21]. For example, under ALAN molecular markers for sleep deprivation were elevated, hypothalamic expression of genes such as TLR4 was altered [16], neuronal features in the brain were changed, and cognitive processes and mental health-like states were impaired [16,20,56,57].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors have even shown that, for these taxa, ALAN poses a threat equivalent to others such as soil artificialization and the proportion of intensive agriculture on a large scale (Azam et al 2016). Such spatial and temporal perturbation of habitats and species is suspected in turn to profoundly affect the functioning dynamics of populations, communities, and ecosystems (Falcón et al 2020).…”
Section: The Ecological Implications Of Alanmentioning
confidence: 99%
“…To test for the effect of ALAN wavelengths on single species growth and assemblage biomass and diversity we run two concurrent experiments from 23/11/2021 and for a period of 18 days: Since algae use light as a source of both information and energy (Bennie, Davies, Cruse, & Gaston, 2016;Falcón et al, 2020), light treatments were standardised to irradiance levels rather than illuminance levels. Daytime light irradiance was 6.5 Watt m -2 and was provided by a 10W flood light (Prolite, Ritelite Systems Ltd, UK) equipped with two arrays of high-power LEDs (6,000K).…”
Section: Experimental Set Up and Light Sourcesmentioning
confidence: 99%